Treinamento físico durante a recuperação nutricional não afeta o metabolismo muscular da glicose de ratos - Santhiago, Vanessa [UNESP]; Da Silva, Adelino Sanchez Ramos [UNESP]; Gobatto, Claudio AlexandreMaria Alice Rostom [UNESP]; De Mello, Maria Alice Rostom [UNESP] (My University, 2006)
This study had the main aim to assess the food intake, the weight gain, and the muscular glucose metabolism in rats submitted to aerobic training while recovering of protean malnutrition. For this, 60 male Wistar rats were separated in two groups: normoprotean (NP) and hypoprotean (HP), according to the diet: NP (17% protein), or HP (6% protein), respectively, which was received after the ablactation (21 days) on their 90th day of life. Then, very animal received the NP diet, and they were submitted or not (trained - TRA; sedentary - SED) to physical training that consisted in running on a treadmill for 25 m/min., 50 min/day for 5 days a week for 30 days, compounding the NP-SED, NP-TRA, HP/NP-SED, and HP/NP-TRA groups. The glucose metabolism was assessed in slices of the soleum muscle incubated in the presence of insulin (100 μU/L), and glucose (5.5 mM containing glucose [C14], and 2-deoxyglycose [H3]). The daily food intake (g/100 g of the body weight) for the HP/NP-TRA group (24.39 ± 4.07) was larger than the HP/NP-SED group (21.62 ± 4.69). The weight gain (g) was similar in both groups HP/NP-TRA (203.80 ± 34.03) and HP/NP-SED (214.43 ± 30.54). There was no difference between both groups in relation to the following parameters: glucose uptake and oxidation, and glycogen synthesis by the soleum muscle. Thus, it can be concluded that the aerobic training did not have any impact on the nutritional recovery, as there was no metabolic or somatic differences among recovered animals in the presence or absence of the training.
Physical training during nutritional recovery does not affect the muscular glucose metabolism in rats
Keywords: Nutritional recovery; Protean malnutrition; Training